Tingkatkan Hasil Belajar Matematika Pokok Bahasan Operasi Hitung Penjumlahan dan Pengurangan Bilangan Bulat Melalui Alat Peraga Kartu Berwarna “Kabe” - Abdul Razak; Rumainur Rumainur (Universitas Veteran Bangun Nusantara, 2022)
The purpose of this study was to improve the mathematics learning outcomes of the subject of arithmetic operations, addition and subtraction of integers through the “Kabe”colored card props. This type of research is classroom action research with a qualitative approach. The procedure of this research includes planning, implementation, observation, and reflection. The data collection techniques used are tests, observations, documentation, and field notes. The data were analyzed quantitatively and qualitatively with the target indicator of success reaching 65% classically with the minimum score obtained by each student being 70. The results of the pre-cycle study showed that the average percentage of completeness was 0% then started to increase to 21.05% (4 students) in the first cycle and 68.42% (13 students) in the second cycle. These results indicate that there has been an increase in students' mathematics learning outcomes on the subject of integers through the use of KaBe teaching aids. So it can be concluded that the KaBe teaching aids can improve students' mathematics learning outcomes.